Genome-wide identification, transcriptional profiling, and miRNA-binding site analysis of the LBD gene family in the camphor tree - Zhang, Jiaqi; Shan, Luyang; Qi, Haoran; Chen, Caihui; Zhong, Yongda; Xu, Meng (Frontiers in Plant Science, 2025)
Cinnamomum camphora (Lauraceae), an evergreen arborescent species endemic to East Asian ecosystems, is ecologically and economically prized for three cardinal attributes: decay-resistant xylem, aesthetic canopy architecture, and pharmacologically active terpenoid emissions. The plant-specific Lateral Organ Boundaries Domain (LBD) transcription factors mediate phylogenetically conserved developmental pathways governing lateral organogenesis and secondary metabolism across embryophytes. Despite multiple published C. camphora genome assemblies, functional characterization of LBD transcription factors in this species remains limited. We systematically identified 40 LBD genes through whole-genome analysis and characterized their structural features, evolutionary relationships, and expression patterns. Five are intron-free, while seven genes harbor two or more introns each. Detailed annotation of CcLBD promoter regions identified 33 cis-regulatory elements linked to hormone signaling and stress adaptation. Transcriptional dynamics of the 40 CcLBD genes were profiled across seven tissues of the camphor tree using short-read RNA-Seq, revealing that 22 genes were highly expressed in flowers and 12 were predominantly expressed in roots, suggesting potential roles in reproductive organ development and root formation in C. camphora. Phylogenetic analysis classified all CcLBD proteins into two clades, each harboring a conserved lateral organ boundaries (LOB) domain. Integrative omics analyses (small RNA-seq and degradome data) further implicated miR408 and miR2950c in post-transcriptional regulation of CcLBD5 via mRNA cleavage. These results establish a framework for the functional dissection of LBD-mediated developmental and stress-response pathways in C. camphora.